FIKIH SIBER: KONSTRUKSI NORMATIF HUKUM ISLAM TERHADAP KEJAHATAN KECERDASAN BUATAN - mahdiyan nasikhin; Ika Puspita Manah; Ainaya Tullah (Universitas Islam Bunga Bangsa Cirebon, 2026)
The rapid advancement of artificial intelligence (AI) technology has introduced novel forms of cybercrime that existing legal frameworks including Islamic jurisprudence have yet to fully address. This study examines the normative construction of Islamic law (fiqh) in responding to AI-generated crimes within the contemporary digital landscape. The primary objective is to identify foundational Islamic legal principles applicable to cybercrime facilitated by artificial intelligence and to formulate a coherent jurisprudential framework referred to as Cyber Fiqh (Fikih Siber). Employing a qualitative library research methodology, this study draws upon classical Islamic legal texts, contemporary fatwa documents, and peer-reviewed academic literature published within the last five years. Data were collected through systematic documentation and analyzed using content analysis and interpretive legal reasoning (ijtihad). The findings reveal that Islamic jurisprudence possesses robust principles—including maqashid al-syariah, maslahah mursalah, and the prohibition of dharar (harm)—that can be systematically applied to regulate AI-driven crimes such as deepfake manipulation, algorithmic fraud, autonomous cyberattacks, and AI-assisted surveillance. This study contributes to the emerging discourse on digital Islamic ethics and offers practical normative guidelines for Islamic educational management institutions navigating the challenges of the AI era.